2017
DOI: 10.3390/jcm6010004
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia: Chronic Lung Disease of Infancy and Long-Term Pulmonary Outcomes

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic lung disease most commonly seen in premature infants who required mechanical ventilation and oxygen therapy for acute respiratory distress. While advances in neonatal care have resulted in improved survival rates of premature infants, limited progress has been made in reducing rates of BPD. Lack of progress may in part be attributed to the limited therapeutic options available for prevention and treatment of BPD. Several lung-protective strategies have been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
263
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(282 citation statements)
references
References 178 publications
3
263
0
16
Order By: Relevance
“…Since the criteria to define BPD still lack uniformity, we reported the composite outcome for both the earliest clinical definition of BPD as oxygen dependency at 28 days and the modified one as the need for oxygen therapy at 36 weeks corrected GA 32. To prevent misclassification in further analysis, we just focused on the second definition.…”
Section: Methodsmentioning
confidence: 99%
“…Since the criteria to define BPD still lack uniformity, we reported the composite outcome for both the earliest clinical definition of BPD as oxygen dependency at 28 days and the modified one as the need for oxygen therapy at 36 weeks corrected GA 32. To prevent misclassification in further analysis, we just focused on the second definition.…”
Section: Methodsmentioning
confidence: 99%
“…Among the developmental lung diseases, BPD is the most common and important cause. BPD is the most common morbidity of children born <30 weeks’ gestation and remains the most common lung disease of infancy . BPD is diagnosed in roughly 40% of infants born ≤28 weeks gestational age, which results in 10 000‐15 000 new cases in the USA each year .…”
Section: Neonatal Phmentioning
confidence: 99%
“…8 Adults who had BPD as infants are at increased risk for subclinical right ventricular dysfunction, obstructive lung disease, exercise intolerance, emphysema, asthma-like symptoms, and reduced quality of life due to respiratory symptoms. 6 One study found that these adults were twice as likely to report wheezing and three times more likely to use asthma medications than controls. 9 Is an elevated ETCO 2 on a neonatal PSG a biomarker for neurodevelopmental outcome?…”
mentioning
confidence: 99%
“…BPD appears to be caused by varying combinations of maternal chorioamnionitis or preeclampsia, postnatal mechanical ventilation, hyperoxia, and inflammation in infants born extremely premature. 6 Of note, BPD develops in only half of extremely premature infants.…”
mentioning
confidence: 99%